2019
DOI: 10.1186/s12884-019-2188-8
|View full text |Cite
|
Sign up to set email alerts
|

Lifting the veil on disrespect and abuse in facility-based child birth care: findings from South West Nigeria

Abstract: BackgroundEliminating disrespect and abuse in health care facilities during childbirth could be a contributory factor in improving pregnancy outcomes and avoiding preventable illnesses and deaths. This study aims to provide evidence of disrespect and abuse in this community in order to create awareness about its occurrence.MethodsA cross-sectional survey was carried out on 384 recently delivered women who visited the postnatal and immunization clinics of a primary and tertiary health facility in Ile-Ife. Infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
19
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 12 publications
5
19
3
Order By: Relevance
“…Our findings are comparable to evidence from previous studies [1,6,10,11]. Although, most women in this study were treated with respect, as much as 20% were verbally abused, which is slightly higher than findings of 11-18% in prior studies [6,10,11], but consistent with high incidence of disrespect and abuse in other studies [12][13][14][15][16][17][18][19]. Similarly, our finding that 7% of women were physically abused was higher than results elsewhere [6,10,11,15], but lower than findings reported in previous studies [12,[16][17][18].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our findings are comparable to evidence from previous studies [1,6,10,11]. Although, most women in this study were treated with respect, as much as 20% were verbally abused, which is slightly higher than findings of 11-18% in prior studies [6,10,11], but consistent with high incidence of disrespect and abuse in other studies [12][13][14][15][16][17][18][19]. Similarly, our finding that 7% of women were physically abused was higher than results elsewhere [6,10,11,15], but lower than findings reported in previous studies [12,[16][17][18].…”
Section: Discussionsupporting
confidence: 90%
“…Although, most women in this study were treated with respect, as much as 20% were verbally abused, which is slightly higher than findings of 11-18% in prior studies [6,10,11], but consistent with high incidence of disrespect and abuse in other studies [12][13][14][15][16][17][18][19]. Similarly, our finding that 7% of women were physically abused was higher than results elsewhere [6,10,11,15], but lower than findings reported in previous studies [12,[16][17][18]. The sharp decrease in physical abuse might reflect underreporting as this behaviour may be accepted as normal and not considered as abuse or disrespect by some women in Nigeria [16], or due to a rising awareness of litigation among care providers [15].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…All three regions of the previous studies were however done in urban settings alone. Evidence from a recent study in another south west state showed a low rate of about 19% and various interventions are likely to reduce D&A where the rates are already high [24]. The present study showed D&A were as high as 75.3% in urban settings unlike 18.3% obtained in rural settings.…”
Section: Discussioncontrasting
confidence: 62%
“…These are similar to findings of Amole et al who reported that most of the respondents were 25-29years with average age of 27.7 ± 6.3, mostly married, housewives, of Hausa ethnic group, but rather a secondary level of education as their respondents were only urban Kano women [17]. The finding defers from those of a study from the South-west Nigeria where more than half of the respondents were in the 30-39 year age group, another half had a tertiary education and of Yoruba ethnic group [24] or another from the south east where mean age of the respondents was 32.1 ± 2.7 years, mainly from the Igbo tribe and more than one third had completed tertiary education [18].…”
Section: Discussioncontrasting
confidence: 61%